أثر الرسوم المتحركة في بناء الخيال عند الطفل - معيزة, سارة; شبرو, إكرام (جامعة الوادي - University of Eloued, 2022)
Abstract: This study aimed to find out the effect of animation through children's channels in building the imagination of the child, through a field study on a sample of children in El OUED state. A problem has also been formulated under the title of the effect of animation in building the imagination of the child This study relied on the descriptive approach, where a questionnaire was designed and distributed to the respondents . The following results were obtained: - Children are greatly exposed to cartoons and interact with them and are greatly affected by them and contribute to the process of their academic achievement andtheir acquisition of new vocabulary and skills - Children resort to the world of imagination to express what they love or dreamabout through cartoon films that increase the capacity of this imagination andnourish it and provide them with a set of ideas and perceptions, which in turncontribute to building the child's personality and mind الملخص: هدفت هذه الدراسة الى معرفة مدى تأثير الرسوم المتحركة عبر قنوات الاطفال في بناء الخيال لدى الطفل ، وذلك من خلال دراسة ميدانية على عينة من اطفال ولاية الوادي . اعتمدت هذه الدراسة على المنهج الوصفي حيث تم تصميم استمارة وتوزيعها على المبحوثين .كما تمت صياغة اشكالية تحت عنوان اثر الرسوم المتحركة في بناء الخيال لدى الطفل . وتم التوصل الى النتائج التالية: - يتعرض الاطفال بشكل كبير الى الرسوم المتحركة ، يتفاعلون معها وتؤثر فيهم بشكل كبير وتساهم في عملية تحصيلهم الدراسي واكتسابهم ممن المفردات والمهارات الجديدة - يلجـأ الاطفال الى عالم الخيال للتعبير عما يحبونه او مايريدونه من خلال افلام الكرتون التي تزيد من سعة هذا الخيال وتغذيه وتمدهم بمجموعة من الافكار والتصورات والتي تساهم بدورها في بناء شخصية الطفل وعقله
دراسة مسحية لعينة من أطفال ولاية الوادي
مذكرة ماستر إعلام وإتصال
Keywords: Animation - building imagination - child; الرسومالمتحركة - بناءالخيال - الطفل